Impact of Inter-fractional Anatomical Changes on Dose Distributions in Passive Carbon-Ion Radiotherapy for Prostate Cancer: Comparison of Vertical and Horizontal Fields - Yokoyama, Ayaka; Kubota, Yoshiki; Kawamura, Hidemasa; Miyasaka, Yuhei; Kubo, Nobuteru; Sato, Hiro; Abe, Satoshi; Tsuda, Kazuhisa; Sutou, Takayuki; Ohno, Tatsuya; Nakano, Takashi (Frontiers in Oncology, 2020)
Purpose: We quantified the inter-fractional changes associated with passive carbon-ion radiotherapy using vertical and horizontal beam fields for prostate cancer. Methods: In total, 118 treatment-room computed tomography (TRCT) image sets were acquired from 10 patients. Vertical (anterior–posterior) and horizontal (left–right) fields were generated on the planning target volume identified by treatment planning CT. The dose distribution for each field was recalculated on each TRCT image set at the bone-matching position and evaluated using the dose–volume parameters for the prostate and rectum V95 values. To confirm adequate margins, we generated vertical and horizontal fields with 0-, 2-, 4-, and 6-mm isotropic margins from the prostate and recalculated the dose distributions on all TRCT image sets. Sigmoid functions were fitted to a plot of acceptable ratios (that is, when prostate V95 > 98%) versus the isotropic margin size to identify the margin at which this ratio was achieved in 95% of patients with a vertical or horizontal field. Results: The prostate V95 values (mean ± standard deviation) were 99.89 ± 0.62% and 99.99 ± 0.00% with vertical and horizontal fields, respectively; this difference was not statistically significant (p = 0.067). The rectum V95 values were 1.93 ± 1.25 and 1.88 ± 0.96 ml with vertical and horizontal fields, respectively; the difference was not statistically significant (p = 0.432). The estimated adequate margins were 2.2 and 3.0 mm for vertical and horizontal fields, respectively. Conclusions: Although there is no significant difference, horizontal fields offer higher reproducibility for prostate dosing than vertical fields in our clinical setting, and 3.0 mm was found to be an adequate margin for inter-fractional changes.